The Influence of Legislation and Regulation on Strategy in Public Entities - Govender, Kasavan; Draai, Enaleen; Taylor, Derek (Journal of Reviews on Global Economics, 2018)
In terms of prescriptions contained in the Constitution of the Republic of South Africa, 1996, citizens are entitled to, inter alia, the provision of services in a sustainable manner. Citizens are also entitled to the promotion of social and economic development to meet their basic needs. Government designs systems and processes to meet those needs in response to policy goals and objectives as defined in legislation and regulation in the context of the principal-agent approach. Similarly, strategy is needed to devise techniques and plans to meet needs, goals and aspirations of government in the most efficient manner. It is premised on leadership, goal orientation and satisfying a multitude of factors in the process. At face value it would seem that the enactment of certain legislation and regulations appear to render the need for strategy obsolete, especially since there is a proliferation of national, provincial and local policies and strategies that only need implementation. This article reviews the influence of legislation and regulations on strategy in public entities, focusing on a development corporation in the Eastern Cape as a case study. For purposes of data collection a mixed-methods research methodology approach was followed. The article concludes with a proposed normative model to enhance strategy in public entities.